2023
DOI: 10.5603/pjnns.a2022.0078
|View full text |Cite
|
Sign up to set email alerts
|

Could hyperlipidemia be a risk factor for corticobasal syndrome? — a pilot study

Abstract: Introduction.Corticobasal syndrome (CBS) is a specific clinical manifestation shared by multiple pathologies. The exact mechanism of this phenomenon remains unclear. Differential diagnosis of CBS in everyday clinical practice is challenging, as this syndrome can overlap with other entities, especially progressive supranuclear palsy Richardson-Steele phenotype (PSP-RS). Several papers have suggested a possible role of vascular pathology as a linking factor in the pathogenesis of CBS based on different neuropath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…MRI findings in CBD may include high signal intensity in subcortical white matter on diffusion weighted image (DWI) and fluid-attenuated inversion recovery (FLAIR), reflecting pathological changes in subcortical white matter [ 17 ]. Furthermore, it is important to consider cerebrovascular disease when attempting to determine the cause of FCMS and CBS, since cerebrovascular disease can cause FCMS and CBS [ 1 ], and some reports have suggested that vascular pathology may be involved in the development of CBS [ 18 ]. In the present case, FLAIR showed only faint high signal intensity lesions in the subcortical region of the frontal lobe and no prominent white matter lesions.…”
Section: Discussionmentioning
confidence: 99%
“…MRI findings in CBD may include high signal intensity in subcortical white matter on diffusion weighted image (DWI) and fluid-attenuated inversion recovery (FLAIR), reflecting pathological changes in subcortical white matter [ 17 ]. Furthermore, it is important to consider cerebrovascular disease when attempting to determine the cause of FCMS and CBS, since cerebrovascular disease can cause FCMS and CBS [ 1 ], and some reports have suggested that vascular pathology may be involved in the development of CBS [ 18 ]. In the present case, FLAIR showed only faint high signal intensity lesions in the subcortical region of the frontal lobe and no prominent white matter lesions.…”
Section: Discussionmentioning
confidence: 99%